Using a PSCAD simulation software in calculating the probability of surge protective devices failure in an installation served by overhead lines - Hamzah I.; Ramli A.Q. (2023)
Surge protective devices (SPDs) are used in protecting low voltage distribution networks against lightning strike. Lightning strike not only produces overvoltage but also comes with discharge current. Even if the voltage is clamped by the SPD, the discharge current from the lightning strike may cause SPD to fail. Normally, people look at clamping voltage (voltage protection level) without looking properly at the maximum allowable energy of SPD. This paper looks in the SPDs failure on the low voltage installation which been served by overhead lines. In this paper, the work is done in order to calculate the probability of SPDs failure based on the actual lightning data in Malaysia. The peak current is a probability phenomenon. By looking at the probability of lightning peak current and location of those lightning activities, it is possible to calculate the kind of induced voltage to appear on the electrical installation. From the calculated results, a better selection of SPD size to be installed can be assured. 2011 IEEE.